Effect ofsavory(Satureja hortensis L.) and tarragon(Artemisiadracunculus L.) residues on germination and growth of oats (Avena fatua L.) - لیلا نورانی; آنیتا نماینده (علوم و فناوری بذر ایران)
Due toproblems arising from the use of natural methods acceptable herbicides for weed control has been identified. Allelopathyby releasing allochimical be one way to control weeds is worthwhile.  In order to show the effects of aqueous extracts of Tarrgon  and Savory on germination and growth of weeds Savory  Oats seed  in greenhouse, in College of Agricultural of azad university of shiraz, shiraz, Fars provenice, Iran wasconducted.experimentin a randomized complete block design with three replications and three factors were performed(The first factorin both savory and tarragon plant surface and the second factor and the third factor 4 levels in both leaf and stem). 7, 9, 11 and 13 days after sowing germinated seeds counted and the various parameters, was measured. resultsindicated that theuse ofsavory andtarragonleaves andstems of plantsmay reducethegermination andearly growthtraitsandoatsvehiclehas affected.SavoryTarragonplantdebriseffectwas moreandmoretraitshas reducedby 6%. A recentevaluationofallelopathiceffectsonweeds,crop residues, andothermaterialstoreduce reliance onherbicidesisnormaldamage. Future studies of this plant can be used to control weeds, oats .